Future needs for continuing innovation in hemophilia: improving outcomes for individuals of all severities, including women and those in resource-constrained regions - Blatný, Jan; Astermark, Jan; Catarino, Cristina; Dolan, Gerry; Fijnvandraat, Karin; Hermans, Cédric; Holstein, Katharina; Jiménez-Yuste, Víctor; Klamroth, Robert; Lavin, Michelle; Lenting, Peter J; Lobet, Sébastien; et al. (Therapeutic advances in hematology, 2024)
Over recent decades, management of people with hemophilia (PwH) has been greatly improved by scientific advances that have resulted in a rich and varied therapeutic landscape. Nevertheless, treatment limitations continue to drive innovation, and emerging options have the potential to realize further improvement. We advocate four general principles to optimize benefits from innovation: individualizing the treatment approach, targeting 'normal,' making the most of available resources, and considering treatment affordability. Ultimately, all PwH-men and women, of all ages and severities, and worldwide-should have access to treatment that fully prevents bleeding, while allowing personal, social, family, and professional lives of choice. Clearly, we are not there yet, but developing goals/milestones based on the principles we describe may help to achieve this.